2021
DOI: 10.1029/2021gc009703
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Properties of the Pyrite‐Type FeOOH‐AlOOH System From First‐Principles Calculations

Abstract: Hydrogen storage and cycling in the deep Earth have important implications on the chemistry and dynamics of Earth's mantle. Recent results suggest a likely carrier of hydrogen into the Earth's lower mantle is the solid solution formed by the isostructural series ϵ-FeOOH, δ-AlOOH, and phase H (MgSiO 4 H 2 ) (Kawazoe et al., 2017;Nishi et al., 2017;Ohira et al., 2014). At higher pressure, CaCl 2 -type δ-AlOOH is predicted to transform into a pyrite structure (Tsuchiya & Tsuchiya, 2011) consisting of an AlO 2 fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(142 reference statements)
0
3
0
Order By: Relevance
“…These compositions could serve as possible contributors to ULVZs. ULVZs have multiple proposed explanations, including FeSi formed through core‐mantle reactions (Mergner et al., 2021), hydrous phases such as (Al,Fe)OOH (Thompson et al., 2021), Fe‐rich post perovskite (Garnero & McNamara, 2008), Fe‐rich (Mg,Fe)O (Solomatova et al., 2016; Wicks et al., 2010), and patches of partial melt (Williams & Garnero, 1996). Partial melt is a likely explanation for ULVZs due to the 3:1 ratio of S‐to‐P wave velocity reduction (Garnero & McNamara, 2008; Williams & Garnero, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…These compositions could serve as possible contributors to ULVZs. ULVZs have multiple proposed explanations, including FeSi formed through core‐mantle reactions (Mergner et al., 2021), hydrous phases such as (Al,Fe)OOH (Thompson et al., 2021), Fe‐rich post perovskite (Garnero & McNamara, 2008), Fe‐rich (Mg,Fe)O (Solomatova et al., 2016; Wicks et al., 2010), and patches of partial melt (Williams & Garnero, 1996). Partial melt is a likely explanation for ULVZs due to the 3:1 ratio of S‐to‐P wave velocity reduction (Garnero & McNamara, 2008; Williams & Garnero, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…ULVZs have multiple proposed explanations, including FeSi formed through core-mantle reactions (Mergner et al, 2021), hydrous phases such as (Al,Fe)OOH (Thompson et al, 2021), Fe-rich post perovskite (Garnero & McNamara, 2008), Fe-rich (Mg,Fe)O (Solomatova et al, 2016;Wicks et al, 2010), and patches of partial melt (Williams & Garnero, 1996). Partial melt is a likely explanation for ULVZs due to the 3:1 ratio of S-to-P wave velocity reduction (Garnero & McNamara, 2008;Williams & Garnero, 1996).…”
Section: Gibbs Free Energy Of Mixingmentioning
confidence: 99%
“…However, the formation of pyritetype AlOOH remains unverified, highlighting the need for further high-pressure, high-temperature experiments. Recent high-pressure experiments propose that δ-AlOOH, which is structurally similar to phase H, could remain stable in the lower mantle (Thompson et al, 2021). It has also been shown that Al can separate from bridgmanite and CaSiO 3 perovskite to form δ-AlOOH in the presence of H 2 O.…”
Section: Introductionmentioning
confidence: 99%